Initial viral load in cases of single human papillomavirus 16 or 52 persistent infection is associated with progression of later cytopathological findings in the uterine cervix. Issue 12 (19th August 2013) - Hamaguchi, Daisuke; Miura, Kiyonori; Abe, Shuhei; Kinoshita, Akira; Miura, Shoko; Yamasaki, Kentaro; Yoshiura, Koh‐ichiro; Masuzaki, Hideaki
Abstract The aim of this study was to investigate the relationship between viral load in single human papillomavirus (HPV) 16 or 52 persistent infection and the progression of later cytopathological findings in the uterine cervix. Cervical cytology and HPV genotyping tests were repeated within 3–6 months in 305 women with oncogenic HPV. Twenty‐four cases of single HPV 52 persistent infection and 24 cases of single HPV 16 persistent infection were identified. Cases with later cytopathological findings showing progression were defined as the progression group, while those with no change or regression were the non‐progression group. Relative HPV DNA loads were determined by quantitative real‐time polymerase chain reaction and expressed relative to human albumin (ALB) DNA. Differences between the two groups were evaluated. The median relative HPV 52 DNA load was 2.211 in the progression group and 0.022 in the non‐progression group (Mann–Whitney U‐test, P = 0.003). The median relative HPV 16 DNA load was 4.206 in the progression group and 0.103 in the non‐progression group (P = 0.001). HPV 52 and 16 DNA loads assessed by quantitative real‐time methods may be useful short‐term markers for identifying women at high risk for progression of cervical cytological pathology. J. Med. Virol. 85:2093–2100, 2013. © 2013 Wiley Periodicals, Inc.